KAMERA CLOSED CIRCUIT TELEVISION (CCTV) SEBAGAI BENTUK PERLINDUNGAN PASIEN TERHADAP PELECEHAN SEKSUAL : DILEMA ANTARA HAK PRIVASI DAN KEAMANAN PASIEN - Ginting, James; MP, HM Rezky Pahlawan (Rechtsregel : Jurnal Ilmu Hukum, 2025)
The increasing number of sexual harassment cases involving individuals from the medical profession has understandably raised significant concerns among prospective patients seeking medical treatment. This situation has resulted in negative impacts for both parties, patients, who may experience psychological distress and anxiety, and the medical profession, which is facing a decline in public trust. This study aims to examine the use of Closed-Circuit Television (CCTV) within medical examination rooms as a preventive measure against sexual harassment committed by medical practitioners, as well as to analyze this policy from the perspective of the prevailing health law in Indonesia. The research problem is formulated as follows: how the installation of CCTV in medical examination rooms can serve as a protective mechanism to reduce the potential for sexual harassment by medical personnel, and how such implementation aligns with the existing legislative framework in Indonesia. This research adopts a literature review method, relying on secondary sources such as books, academic journals, and other legal materials. The collected data is analyzed through the application of legal theories to address the research questions posed in this study. Based on the findings of this research, it can be concluded that there is no specific regulation prohibiting the installation of Closed-Circuit Television (CCTV) within medical examination rooms. Therefore, its use may be considered as an auxiliary tool for monitoring and preventing sexual misconduct by medical practitioners. However, its implementation must be approached with caution, given that the data recorded by CCTV constitutes Electronic Information governed by the Electronic Information and Transactions Law (ITE Law), and, when related to the Personal Data Protection Law, such data also qualifies as personal data that must be protected. In cases of misuse of such data, patients who suffer harm may pursue legal remedies under the applicable laws.